Improved catalyst regeneration process to increase poison removal and improve performance recovery - Bauza, Rodrigo, author; Olsen, Daniel, advisor; Windom, Bret, committee member; Johnson, Jerry, committee member (Colorado State University. Libraries, 2021)
Internal combustion engines are partly responsible for increasing amounts of carbon dioxide, nitrogen, carbon monoxide, hydrocarbons, aldehydes, and particulate matter in the atmosphere. These emissions have detrimental health effects on humans and negatively impact the environment by contributing to the formation of acid rain and photochemical smog. Large bore two-stroke natural gas engines are used commonly for power generation, and in order to meet the National Emissions Standards for Hazardous Air Pollutants set by the Environmental Protection Agency, engine manufacturers commonly select oxidation catalysts as the exhaust aftertreatment of choice. These catalysts degrade over time due to thermal, chemical, and mechanical reasons. Lubrication oil makes its way through the combustion chamber and onto the catalyst, degrading the unit. To estimate the degradation rate of the units and to find the best restoration method, two identical alumina-platinum oxidation catalysts were used in a dual setting, combining a field degradation engine and a laboratory testing engine. The lubrication oil from the cylinder makes its way to the catalyst and creates a layer of volatile hydrocarbons at the very surface that reduces the surface area and catalytic activity of the unit. Moreover, the additives from the oil, such as sulfur, phosphorus, and zinc actively poison the crystallites and minimize the reduction efficiency of the units. The wash-coat is turned into a powder and analyzed, showing sulfur is the most prevalent poison, constituting approximately 8.97% of the wash-coat when the units are degraded. Phosphorus constitutes roughly 2.55%, and zinc makes up less than 0.50% of the wash-coat and is the most superficial poison. Sulfur is not only the most prevalent but also penetrates deeper into the wash-coat than the rest of the poisons, but phosphorus is seen to interact chemically with the platinum crystallites, suggesting a stronger de-activation by phosphorus. Platinum is more active in its metallic form, and the catalyst of interest improves in performance after being chemically reduced in a 5% hydrogen purge at 450°C, indicating the platinum crystallites were oxidized in the aging process. The units were aged, then restored with the industry standard washing procedure, then aged again until reaching non-compliance with the emissions standards set by the Environmental Protection Agency, and then restored a second time with a modified version of the industry standard washing process. In order to find the best restoring process, variations of the industry standard chemical wash are tested, and the result proves unsuccessful to modify the washing procedure. Moreover, the industry standard washing process is enhanced by adding two new steps, carbon baking and crystallite restoration. The combination of both baking and washing is tested with elemental and performance analysis. The laboratory elemental analysis suggests the baking restoration steps should be added before washing, which is in agreement with the performance bench testing results. The levels of sulfur and phosphorus are respectively brought down to 0.692% and 0.689% after applying the modified restoration process to the units, and zinc is reduced to 0.048% of the wash-coat. However, the slipstream performance results with real exhaust from a Cummins QSK19G do not fully agree with the addition of the baking steps to the industry washing standard restoration, likely because the combined restoration was tested on a catalyst that had been previously washed and re-aged, which is known in the industry to produce less successful restoring results. The catalysts can be aged and restored two to three times before the reduction efficiency increase from the restoration is not great enough to financially motivate catalyst users to restore the units instead of replacing them.